Creating a shared scientific culture to further design a theoretical online tutoring model: learning from past experience - Brudermann, Cédric; Adé, David (Swiss Journal of Educational Research, 2020)
A French multidisciplinary research team has worked on the design of a theoretical online tutoring model. This effort – which required that a shared scientific culture be created in the first place – is far from being self-evident and can prove to be a contentious issue as it brings together researchers from various domains into a common effort. In this project, in order to foster multidisciplinary research collaboration, the three interrelated dimensions (mutual engagement, shared repertoire and joint enterprise) around which – according to Lave and Wenger (1991) – communities of practice are organized, were used as guidelines. In this paper, we illustrate how the three dimensions underlying this theory were relied upon to carry out this collective scientific endeavor. A critical overview of this multidisciplinary research experience is then provided